IMPACT RANKINGS 2024 : Report Dmytro Motornyi Tavria State Agrotechnological University - (:unkn) unknown (TSATU, 2025)
Ukraine continues to demonstrate an indomitable will in the face of full-scale war, overcoming daily challenges and restoring what has been destroyed with resilience and unity. Despite the relocation of our university, TSATU has not only preserved but significantly strengthened its educational and scientific activities, remaining steadfast in its commitment to the Sustainable Development Goals and demonstrating an unwavering resilience. According to the results of 2024, Dmytro Motornyi Tavria State Agrotechnological University made a significant contribution to strengthening institutional stability, advancing technological development and supporting the integration of Ukraine into the global space. Quality education remains our highest priority. Educational programs at TSATU are continuously adapted to ensure the uninterrupted delivery of learning, even in times of crisis, contributing to the training of highly qualified specialists for enterprises across diverse sectors of economic activity. TSATU successfully develops a hybrid model of education, grounded in robust inter-institutional partnerships, while maintaining the continuity of practical training and ensuring the accreditation of educational programmes. With the support of international partners, TSATU is implementing a comprehensive digital transformation of its academic environment, equipping modern laboratories and promoting strategically important areas of specialist training, particularly by expanding access to engineering, technical, and agrotechnological specialities. We make deliberate investments in priority areas of specialist training, focusing on preparing graduates who are not only ready to embrace innovation but also to create it. We are convinced that economic growth begins with equality and respect. Our contribution to strengthening practices that ensure decent work, economic development, and innovation is valuable at the regional, national, and international levels. In the field of ensuring gender equality and social inclusion, TSATU has officially consolidated its Policy on Non-Discrimination, reinforcing the career and academic development of women. TSATU scientists successfully defended Doctor of Philosophy theses and received high academic honours, clearly demonstrating the effectiveness of institutional support for women’s leadership in higher education and research. The university staff actively develops dual education models in partnership with leading enterprises, and integrates advanced IT solutions into the educational process. TSATU scientists have received state funding from the Ministry of Education and Science, secured patents for intellectual property related to agricultural innovations, and actively participate in international scientific and practical events (conferences, seminars, forums, etc.). Our ongoing search for effective approaches to science–business synergy is strategically focused on shaping post-war recovery model. Internationalisation processes and the development of global partnerships serve as key drivers for the exchange of best practices and the generation of innovative solutions. Partnership has become a cornerstone of institutional sustainability for TSATU. We have strengthened cooperation with the global academic community and contributed meaningfully to the achievement of the Sustainable Development Goals by engaging student leaders and providing expert support to regional authorities, business stakeholders and non- governmental organisations. We firmly believe that education and science must serve as accelerators for building a peaceful society. We actively promote the values of tolerance, justice, and mutual respect. In advancing peace, justice, and strong institutions, TSATU team and students demonstrate a high level of civic consciousness, ensuring elected representation of diverse groups within university governance structures. The university acts as an initiator of neutral platforms for the discussion of socially significant issues, upholding the principles of freedom of speech and the protection of human rights. TSATU remains firmly committed to its mission: the training of highly qualified, patriotic, and sustainability-oriented specialists capable of contributing to the rebuilding and development of Ukraine in alignment with the Sustainable Development Goals. We recognise the significance of our collective efforts and the enduring contribution of TSATU to shaping a sustainable and just future. The daily work of our university team reflects a deep commitment to protecting the quality of life for future generations.
IMPACT RANKINGS 2024 : ЗВІТ Таврійського державного агротехнологічного університету імені Дмитра Моторного
Keywords: Sustainable Development Goals (SDGs); Quality Education; Gender Equality; Decent Work and Economic Growth; Innovation and Infrastructure; Life on Land; Peace an Juctice; Partnership for the Goals; Dmytro Motornyi Tavria State Agrotechnological University